2007
DOI: 10.1118/1.2745921
|View full text |Cite
|
Sign up to set email alerts
|

Visibility of microcalcification in cone beam breast CT: Effects of x‐ray tube voltage and radiation dose

Abstract: Mammography is the only technique currently used for detecting microcalcification (MC) clusters, an early indicator of breast cancer. However, mammographic images superimpose a three-dimensional compressed breast image onto two-dimensional projection views, resulting in overlapped anatomical breast structures that may obscure the detection and visualization of MCs. One possible solution to this problem is the use of cone beam computed tomography (CBCT) with a flat-panel (FP) digital detector. Although feasibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 37 publications
0
61
0
Order By: Relevance
“…The visibility of MCs in cone beam breast CT with a flat panel ͑FP͒ detector has been investigated and reported. 12,[14][15][16] It was reported that the visibility of large MCs ͑ ജ 250 m͒ increased with increasing mean glandular dose, while the small MCs ͑ Ͻ 250 m͒ were invisible probably due to the limited sensitivity of the FP detector and spatial resolution of the imaging system.…”
Section: Introductionmentioning
confidence: 99%
“…The visibility of MCs in cone beam breast CT with a flat panel ͑FP͒ detector has been investigated and reported. 12,[14][15][16] It was reported that the visibility of large MCs ͑ ജ 250 m͒ increased with increasing mean glandular dose, while the small MCs ͑ Ͻ 250 m͒ were invisible probably due to the limited sensitivity of the FP detector and spatial resolution of the imaging system.…”
Section: Introductionmentioning
confidence: 99%
“…19 Although an early simulation study indicated that MCs as small as 175-200 μm could be visible in flat panel-based breast CT when the mean glandular dose (MGD) is kept at an acceptable level, a later experimental study reported that the minimum detectable MC size was about 308 μm at the 75% visibility level under similar exposure conditions. 18,20,21 Using a high resolution (48 μm pitch) CCD detector, we have demonstrated that MCs as small as 150 μm could be visualized at an elevated x-ray exposure level. 22 However, it is essential to be able to improve the ability of the BCT system to image small MCs with MGDs as low as 6 mGy.…”
Section: Introductionmentioning
confidence: 95%
“…Optimization and selection of the x-ray spectrum for breast CT has been previously investigated with various conclusions. 15,18,[23][24][25][26] Some of these studies suggested that lower kVs would result in better performance in optimizing the calcification contrast. 24,26 Our own study, based on direct evaluation of MC visibility, did not find any statistically significant improvement when using 60 kV x-rays instead of 80 kV xrays.…”
Section: C Image Acquisition and Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson Cancer Center. 40,41 CT image data used in this study were obtained from investigators at the University of California at Davis as part of an IRB approved study using a prototype dedicated breast CT scanner.…”
Section: Iib Breast Ct Data Acquisition and Image Processingmentioning
confidence: 99%